Manual of romance languages in Africa - Reutner, Ursula (De Gruyter, 2024)
With more than two thousand languages spread over its territory, multilingualism is a common reality in Africa. The main official languages of most African countries are Indo-European, in many instances Romance. As they were primarily brought to Africa in the era of colonization, the areas discussed in this volume are thirty-five states that were once ruled by Belgium, France, Italy, Portugal, or Spain, and the African regions still belonging to three of them. Twenty-six states are presented in relation to French, four to Italian, six to Portuguese, and two to Spanish. They are considered in separate chapters according to their sociolinguistic situation, linguistic history, external language policy, linguistic characteristics, and internal language policy. The result is a comprehensive overview of the Romance languages in modern-day Africa. It follows a coherent structure, offers linguistic and sociolinguistic information, and illustrates language contact situations, power relations, as well as the cross-fertilization and mutual enrichment emerging from the interplay of languages and cultures in Africa.
MRL 32
Keywords: Linguistik; Postkolonialismus; Sprachgeografie; Romanische Sprachen; Afrika; Aufsatzsammlung